Economic analysis of price premiums in the presence of non-convexities: Evidence from German electricity markets - Martin Heinrich Paschmann (Institute of Energy Economics at the University of Cologne (EWI), 2017)
Analyzing price data from sequential German electricity markets, namely the day-ahead and intraday auction, a puzzling but apparently systematic pattern of price premiums can be identified. The price premiums are highly correlated with the underlying demand profile. As there is evidence that widespread models for electricity forward premiums are not applicable to the market dynamics under analysis, a theoretical model is developed within this article which reveals that non-convexities in only a subset of sequential markets with differing product granularity may cause systematic price premiums at equilibrium. These price premiums may be bidirectional and reflect a value for additional short-term power supply system flexibility.
Keywords: C60; C62; C63; D21; D23; D24; D41; D44; D47; L11; 330; sequential market organization; electricity markets; short-term market dynamics; price premiums; arbitrage